Maternal and Perinatal Health in Developing Countries 2012
DOI: 10.1079/9781845937454.0139
|View full text |Cite
|
Sign up to set email alerts
|

Geographical access, transport and referral systems.

Abstract: Poor access to emergency obstetric care is due to one of three delays: deciding to seek care, reaching a health facility and receiving appropriate treatment. Poor geographical access in itself is not the cause of the second delay, but the delay results from failure to bridge it with adequate referral interventions and systems. Geographical access can be defined using several dimensions, including distribution and density of services, distance and time. Poor physical access to health services contributes to urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…The most prominent type of article included was cohort study, with 19 studies having critical appraisal scores ranging from 55% to 100%. 15,[41][42][43]45,47,[54][55][56][57][58][59][60][61][62][63][64][65][66] For this study type, the greatest concerns were whether confounding factors were identified and dealt with appropriately, as well as whether they used the…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The most prominent type of article included was cohort study, with 19 studies having critical appraisal scores ranging from 55% to 100%. 15,[41][42][43]45,47,[54][55][56][57][58][59][60][61][62][63][64][65][66] For this study type, the greatest concerns were whether confounding factors were identified and dealt with appropriately, as well as whether they used the…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Maternal deaths mostly occur around time of birth from obstetric complications [8]. These complications are often unpredictable and estimated to affect 15% of pregnant women [8,9,10]. Management of obstetric complications requires specialized care of Emergency Obstetric and Newborn Care (EmONC) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These complications are often unpredictable and estimated to affect 15% of pregnant women [8,9,10]. Management of obstetric complications requires specialized care of Emergency Obstetric and Newborn Care (EmONC) [9,10]. The EmONC is a strategy for reducing maternal and neonatal mortality by focusing on identification, referral and treatment of women with obstetric complications [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, our operational definition of access to care, is travel times to care facilities during pre-and/or postnatal care through the referral system triggered through the CLIP trials, from an origin point; a definition which conforms more to addressing the second delay in access to care. References [6,7] articulates the three delays as: delays at home prior to deciding to seek care (the first delay); delays in finding and managing transport to a facility (the second delay); and delays in receiving appropriate treatment once at the facility (the third delay).…”
Section: Introductionmentioning
confidence: 99%